CRYPTOCURRENCY IN NIGERIA: A REVIEW FROM CONTEMPORARY ISLAMIC SCHOLARS’ PERSPECTIVE - Balarabe, Abubakar; Abdullah, Md. Faruk; Abdur Rahman (Jurnal Syariah, 2024)
This study aims to investigate the Sharī‘ah-compliance status of cryptocurrencies in Nigeria, with a particular focus on the Northern region of Arewa. Adopting a qualitative research methodology, the study utilises library research and document analysis to review contemporary Islamic scholars’ perspectives on cryptocurrencies in the region. The findings revealed that while the use of cryptocurrencies is not generally prohibited for public use, financial institutions are restricted from engaging in cryptocurrency transactions. The debate on whether using cryptocurrencies is ḥalāl (lawful) or ḥarām (prohibited) remains contentious, with some scholars classifying it as ḥarām due to concerns regarding their intrinsic value and lack of governmental recognition as legal tender. Such attributes are perceived to pose risks related to gambling, money laundering, and other prohibited activities. The study recommends prudent regulation and management of cryptocurrency by the Central Bank of Nigeria (CBN) and financial institutions in order to gain acceptance among Muslims in Northern Nigeria.